Deep Diving Capabilities and Operational Challenges of Armed Police Force, Nepal - Analysing the Simaltaal Accident (PAAN Journal, 2025)
Nepal's geographical slopes and structure and road construction along the rivers have made road safety a critical concern, on key highways like the Kathmandu-Narayangadh, Karnali, Sunkoshi, etc. In particular, the road from Kathmandu-Narayangadh goes alongside the Trishuli River, and road accidents plunging into the river following are frequently observed on that highway. This study explores the capability of the Armed Police Force (APF), Nepal in deep diving and the operational challenges faced by the rescuers during the rescue operation in the Simaltaal accident, which needs to be addressed by the Government of Nepal for the safety and security of property and people. Because of the high number of incidents due to overspeeding, challenging terrain, and poor infrastructure, the APF, Nepal Disaster Management Training School (DMTS) plays a crucial role in rescuing victims. The research employs a descriptive design, and qualitative approach, employing both primary and secondary data to discuss the capability and operational challenges of deep diving rescuers. The findings reveal that the APF, Nepal's preparedness and response in disaster management particularly, in swift water rescue operations is effective and efficient. The available rescue devices and equipment such as pipe inspection sewer cameras, sound navigation and ranging, sewer, underwater drones, rubber boats, and outboard motors have been utilized effectively in swift water rescue operations. The research concludes with suggestions for further improving disaster rescue operations by providing advanced swift-water rescue devices and equipment, and welfare facilities to the rescuers.